Digital Dialogues of Displacement: Exploring the Role of Whatsapp in Addressing Family Reunification Challenges and Transnational Parenthood Among Pakistani Migrants in Italy - Haider, Syed Imran; Hussain, Iqbal (Italian Sociological Review, 2025)
This study explores the role of WhatsApp in addressing family reunification challenges, promoting emotional well-being, and sustaining transnational parenthood among Pakistani migrants in Italy. Given the complexities of family reunification policies and the emotional toll of long-distance relationships, this research aims to understand how digital communication technologies especially WhatsApp, help migrants navigate these issues and maintain familial bonds across borders. The study employs a sequential mixed-methods approach, combining an online survey conducted through Google Forms with content analysis of WhatsApp group real conversations. The results reveal that WhatsApp serves as a critical tool for transnational families, facilitating real-time communication, emotional support, and the preservation of parental roles despite geographical separation. It also advances the understanding of how digital media not only sustains family ties but also functions as a form of digital kinning, fostering reciprocal care and emotional resilience among transnational migrants. Content analysis identified major areas of difficulty in family reunification including documentation, lengthy procedures and meeting economic requirements and the social networking has been seen as platform to seek support from each other. Such groups need to be guided and encouraged by the relevant stakeholders so the peer-to-peer support mechanisms could be strengthened.